ESD protection design for the gate oxide of an RF-LDMOS - 姜一波 杜寰 曾传滨 韩郑生 (Journal of semiconductors, 2012)
This paper presents the investigation of integrated electrostatic discharge （ESD） protection design for the gate oxide of an RFLDMOS （radio frequency lateral double diffusion MOS）. Through a comprehensive dis cussion of experimental and simulated results, a cascoded NMOS is presented as appropriate integrated gate oxide ESD protection with a high holding voltage and a flexible ESD design window.